Permanent flame-blunted monofilament of middle cerebral artery occlusion technique for ischemia stroke induction in animal models (Faculty of Medicine Universitas Indonesia, 2017)
Background: Rat is the most frequently used animal for ischemic stroke studies. Recently, middle cerebral artery occlusion (MCAO) by introducing various types of surgical monofilament intraluminally has been widely used, with their advantages and disadvantages. For permanent occlusion, problems with mortality in rats are higher than transient. In this study, we used permanent occlusion using modified monofilament by flaming on its tip which may reduce mortality rate, so that chronic phase of stroke can be learned extensively. Methods: Three male Sprague-Dawley rats underwent permanent MCAO. The flame-blunted monofilament was introduced through common carotid artery. Hematoxylin eosin histopathology confirmation and functional assessment post-stroke induction were then evaluated. Results: Evaluation was conducted on 3 rats in different time post-stroke induction (48 hours, 72 hours, and 3 weeks). Using histopathological examination, the infarction was proved in all 3 rats showing red neurons, perivascular edema and neutrophil spongiosis, in infarct and peri-infarct area. The changes in histopathology showed spongiosis were more dominant in 3 week-post-MCAO rats. On the other hand, red neurons and perivascular edema were less compared to 48 and 72-hour-post-MCAO rats. Conclusion: Flame-blunted monofilament showed its efficacy in producing infarct area. The advantages of this technique are easy to perform with simple and less expensive modification of the monofilament. Conducting successful permanent occlusion with less mortality rate will give chances to do further research on stroke in chronic phase and its effect on novel treatment.